Rethinking Religious Pluralism in Islamic Education: A Study on KH. Abdurrahman Wahid’s Perspective in Islamku, Islam Anda, Islam Kita - Rohmah, Aisyah Nur Hidayatur; Bahrozi, Imam; Adam, Saed M (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
The development of Islamic education in Indonesia reflects a dynamic process aligned with the progress of civilization, particularly regarding the importance of diversity in education, which must be instilled in students' daily lives. In this context, Islamic education plays a central role in preserving, maintaining, and passing down values, beliefs, and traditions to future generations. This study aims to explore and deeply analyze the concept of pluralism from the perspective of KH. Abdurrahman Wahid and examine its relevance to contemporary Islamic education. KH. Abdurrahman Wahid is widely recognized as a prominent figure who consistently upholds the values of pluralism, emphasizing the importance of respecting ethnic, religious, and cultural diversity. This research employs a library research method with a qualitative approach, while data analysis is carried out using content analysis techniques on various written sources. The findings reveal that pluralism, according to KH. Abdurrahman Wahid, serves as a fundamental foundation for building a harmonious society. Values such as tolerance, openness, and respect for differences are central to his perspective. In the educational context, this concept has significant implications, including the need for inclusive curriculum development, teaching methods that foster tolerance, and character formation that emphasizes respect for diversity. Therefore, this study recommends integrating the values of pluralism into the education system as an effort to create a peaceful, respectful, and humanistic learning environment.